EVENT MARKETING IN THE REVITALIZING OF TOURISM - Wanagos, Marzena (Acta Scientiarum Polonorum. Oeconomia, 2010)
Events are organized by various actors in the market such as local governments, private businesses, non-profit organizations. In any event, event marketing tool allows you to show the profiles of these actors and may have a particular impact on the creation of the image of the area where the event takes place. Event marketing can be both a tool of tourist products, and promotion tool for the area. Shown examples of the events confirm the thesis that event marketing is a deliberate revival of the economy (growth of demand and supply of services), the popularization of cultural values and the possibility of inclusion of different backgrounds.